Validation of a drooling questionnaire in Indian children with cerebral palsy. (September 2018) - Job, Anjana; Naina, P.; Syed, Kamran Asif; Thomas, Maya; John, Mary; Varghese, Ajoy Mathew
Abstract: Background: Drooling of saliva is a common problem in children with cerebral palsy. In addition to causing impairment in articulation, drooling also affects socialization, interpersonal relationships and integration into society for these children. There are various methods to assess drooling which measure directly the amount of saliva drooled. However the most convenient and popular method is the use of questionnaires which are mostly western based and need slight modification for the Indian scenario Aim-Validation of a modified questionnaire for the assessment of drooling in children with cerebral palsy. Method: The modified questionnaire was administered to parents of children with cerebral palsy willing to participate in the study. The drooling score was compared with objective tests, namely cotton pad test and drooling quotient. Internal consistency was assessed using the Cronbach's alpha, test retest reliability by Intraclass Correlation and sensitivity analysis by the Receiver operating characteristic curve. Results: The modified questionnaire was found to be easy to administer. The Cronbach's alpha coefficient was between 0.867 and 0.879 which implies a high degree on internal consistency. The intraclass correlation and the test retest reliability was found to be statistically significant with a p value < 0.001 which show that the questionnaire was highly reliable for repeat administration as well as administration by different investigators. The ROC Area was found to be 0.94 with a standard error of 0.02 with a 95% confidence interval of 0.88–0.99, which suggests that the score has great specificity, closer agreement between specificity and sensitivity and excellent precision. Conclusion: Our modified questionnaire was easy to administer, highly reliable and valid with high internal consistency. A score of 24 on the questionnaire was found to be the most sensitive and specific point to discriminate between the mild and severe droolers in children with cerebral palsy.